Distribution of Nutritional Status Across Different Age Stages Based on Anthropometric Indices in Bandar Lampung - Annisa Mayang Soliha; Try Any Widyastuti; Marita Pratami; Muhammad Putra Pratama (FKM UIN Sumatera Utara Medan, 2026)
Nutrition remains a public health challenge in Indonesia and can occur at all stages of life, from childhood to old age. Suboptimal nutritional status, whether undernutrition or overnutrition, has the potential to cause short-term and long-term health effects. This study aims to describe the distribution of nutritional status among people of various ages based on anthropometric indices in the Bandar Lampung region. The method used was community service through field practicums assessing nutritional status in five age groups, namely children aged 6–10 years, adolescents aged 11–18 years, adults, women of childbearing age (15–49 years), and the elderly (≥60 years). There were 100 respondents, with each age group consisting of 20 respondents. Anthropometric measurements included weight, height, Body Mass Index (BMI), and Upper Arm Circumference (UAC) in certain groups. The data were analyzed descriptively to examine the distribution of nutritional status in each age group. The results showed that the majority of respondents were in the normal nutritional status category, but malnutrition and overnutrition were still found in all age groups. This condition indicates the existence of a double nutritional burden in the community. This activity is expected to serve as a basis for planning promotional and preventive efforts in the field of public health nutrition.